CREATIVE THINKING SKILLS OF PRE-SERVICE SCIENCE TEACHERS BASED ON THE PISA FRAMEWORK - Agung Mulyo Setiawan; Nuryani Rustaman; Lilit Rusyati; Parlindungan Sinaga (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2026)
Creative thinking is one of the essential skills required in the twenty-first century and constitutes a core component of the pedagogical and professional competencies that teachers are expected to possess. In response to this urgency, this present study aimed to examine the profile of creative thinking among pre-service science teachers using the PISA framework. The research instrument employed three PISA 2022 creative thinking test items to measure creative thinking scores and to classify the creative thinking levels of 61 pre-service science teachers. Within the PISA framework, creative thinking is operationalized through 3 competencies: Generate Diverse Ideas (GDI), Generate Creative Ideas (GCI), and Evaluate and Improve Ideas (EII). A quantitative approach with a cross-sectional research design of population in time was applied in November 2025 and evaluated with the RASCH model, descriptive, and discriminant analysis. The RASCH model analysis indicated high item reliability but low person reliability, which can be attributed to the limited number of test items used in the assessment. The RASCH analysis also confirmed variations in the levels of the GDI, GCI, and EII competencies. Descriptive analysis revealed that the majority of pre-service science teachers were classified within the moderate and low creative thinking categories, while only a small proportion reached the high category based on frequency distribution results. Furthermore, discriminant analysis demonstrated that the GDI and EII competencies served as the primary predictors for classifying individuals into creative thinking categories. This study contributes by providing an empirical overview of the creative thinking skills profile of pre-service science teachers and highlighting the importance of strengthening GDI and EII competencies in the design of science learning in schools.